1996
DOI: 10.1007/bf02364750
|View full text |Cite
|
Sign up to set email alerts
|

Outdoor play in early childhood education settings: Is it safe and healthy for children?

Abstract: Outdoor play is an important and integral part of a high-quality early childhood education curriculum. Outdoor play environments should have equipment that is safe and developmentally appropriate for the children served. The appropriate adult-child ratio should be maintained to prevent unnecessary accidents as well as provide the interaction needed to assist children in developing outdoor physical, social, and language skills. Each facility should have teachers with up-to-date CPR and first-aid training to tak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 1 publication
0
6
0
1
Order By: Relevance
“…Therefore, children's risk-taking decisions are also influenced by supervising adults' evaluations of a situation's risk and their decisions to influence children's risk-taking in play. Research indicates that lack of supervision is a significant cause of childhood injuries in play (Morrongiello, 2005;Morrongiello, Carbett, McCourt, & Johnston, 2006;Rosen & Peterson, 1990;Taylor & Morris, 1996). In accordance with this, studies have shown that children attending childcare centres Á institutions where supervision by adults is typically extensive Á experience fewer injuries than children spending their days at home with their parent(s).…”
Section: Supervision and Early Childhood Education And Care Practitiomentioning
confidence: 80%
“…Therefore, children's risk-taking decisions are also influenced by supervising adults' evaluations of a situation's risk and their decisions to influence children's risk-taking in play. Research indicates that lack of supervision is a significant cause of childhood injuries in play (Morrongiello, 2005;Morrongiello, Carbett, McCourt, & Johnston, 2006;Rosen & Peterson, 1990;Taylor & Morris, 1996). In accordance with this, studies have shown that children attending childcare centres Á institutions where supervision by adults is typically extensive Á experience fewer injuries than children spending their days at home with their parent(s).…”
Section: Supervision and Early Childhood Education And Care Practitiomentioning
confidence: 80%
“…Research has indicated that lack of supervision is one of the causes of childhood injuries in play (Morrongiello, 2005;Morrongiello, Carbett, McCourt, & Johnston, 2006;Taylor & Morris, 1996). In accordance with this, studies have shown that children attending childcare centres, e.g., institutions in which supervision by adults is usually rather extensive, experience fewer injuries than children spending their days at home with their parent(s).…”
Section: Introductionmentioning
confidence: 86%
“…Although no matter what form of entertainment equipment can create a certain value of the game, we should pay more attention to the characteristics of the venue rather than the specific facilities in the venue. Therefore, more and more scholars are beginning to pay attention to the characteristics of the site, such as whether the per capita space is sufficient [19], whether the spatial structure is reasonable [20], and whether the type and structure of the fixed device is humanized [21].Whether the degree of challenge, novelty, and complexity is appropriate [22], the existence of private space [23], the usability of mobile materials or scattered parts [24], etc. Entertainment equipment, practical materials, the challenges of children of all ages, and the opportunity to offer different experiences are all factors that drive high-level games.…”
Section: Insufficient Design Of Children's Outdoor Space Inmentioning
confidence: 99%